Transmitter Station Remote Monitor System Based on Browser /Server Structure - Shanshan Li; Jian Zhou (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Radio and television was an important way for people to acquire information. In order to ensure  the normal work of the transmitter,we used computer to real-time monitor the transmitter working status, find abnormal situation and handle exception in  the broadcast. Transmitter automatic monitoring and controlling system mostly hadn't been constructed or developed remote monitoring system, a few monitoring system  was based on Client/Server  structure. Browser /Server technique had a better development in monitoring field,so we realized the system Based on Browser /Server structure.The Transmitter Station Remote Monitor System Based on Browser /Server structure in the concrete realization had two innovation points:one was that the system of integral logical structure adopts Browser /Server structure of three-layer system, the other was that in the system software code realization, the page dynamic refresh of real-time monitoring and remote print adopted the Ajax technique. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2309